LAS CIFRAS DE JUANA DE AUSTRIA DURANTE LA REGENCIA (1554-1559). - Luo, Wanruo (Estudios Románicos, 2025)
In this paper we offer the research carried out from the ciphers of the Flanders State fund of the General Archive of Simancas (files 507-516) that contain the letters exchanged between Joanna of Austria, her father Charles V and Philip II, her brother, during the years in which he moved to England for his marriage to Mary Tudor and his father Charles V lived in Brussels. Joanna was regent from mid-1554 until the return from the Netherlands of Philip II in the autumn of 1559. Identification of the ciphers they used and their duration.